A Prospective Study on MBBS Student About Different Visual Aids - Choudhary, Raghuveer; Dullo, Puja; Tandon, RV; Gupta, Usha (Journal of Bangladesh Society of Physiologist, 2010)
Background: To enhance successful communication medical teachers are increasingly using different visual aids. Objective: To determine medical students perception of different visual aids like black board (BB), over head projector transparencies (OHPT) and, LCD and to generate recommendations for their optimal use. Methods: A questionnaire based study was carried out among first year MBBS students of Government Medical College, Kota, India. The survey was undertaken among 84 Medical students of first year MBBS of batch 2008 after exposing them to different visual aids like BB, OHPT and LCD in Physiology lectures. A few lectures were absolutely on BB, and some were on OHPT and on LCD. Few classes were taken with mixed visual aids. Students were exposed for such visual aids for one year and then they were requested to complete a questionnaire. Data were statistically analyzed by One Sample Chi-square test. Results: 55 (65.48%) students rated chalk & black board as best visual aids in understanding the topic better as compared to OHPT and LCD (P<0.01). 47 (55.95%) students have good learning experience with black board teaching and it is best mode to note down important points. 56 (66.66%) students favored LCD as more interesting and interactive visual aids (P<0.01). It also complete the lecture faster which was advantageous for 69 (82.17%) students. 77 (91.66%) students wanted mixing of different visual aids (P<0.01). Mostly (75%) do not find any difficulty in switching from one mode to another. No significant gender difference was observed. Conclusion: To improve students learning medical teachers should match the lectures with preferred visual aids. It will maintain interest and enthusiasm among pupil. Key Words: Black board, Teaching, Overhead projector, LCD projector. DOI: 10.3329/jbsp.v4i2.4174 J Bangladesh Soc Physiol. 2009 Dec;4(2): 58-63